Effects of 8 Weeks of Combined Training (Resistance and Endurance) on the Serum Vaspin Level in Obese Girls - Batoul Jalali-Kahnooj; Mohammad Reza Batavani; Mohsen Ghofrani (New Approaches in Sport Sciences, 2019)
Background: Vaspin is an adipokine secreted from fatty tissues that has serious effects on adipose tissues, muscles, liver, and inflammation. Purpose: The study aimed at determining the effects of 8 weeks of combined training (resistance and endurance) on the serum vaspin level in obese girls. Method: The examinees consisted of 25 obese female students (BMI> 30) from Sistan-Baluchestan University in 2016-17 academic years who voluntarily participated in the research. Samples were divided randomly into two groups: Training (n = 13) and Control (n = 12). Combined training group had both resistance training (5 stations of foot press, Lat pulldown, biceps curl, knee flexion and knee extension for 75-70 minutes) and; endurance was running on the treadmill; in the 2 first weeks, with 60% HRmax for 25 minutes, in the 3-6th weeks with 75-65% HRmax for 35 minutes, and in the 6-8th weeks with 75 -85% HRmax for 40 minutes, continuously, for 3sessions each week. Also 10 minutes at the beginning and at the end of the training were warm up and cool down for athletes. It should be noted that during this period the control group did not participate in any kind of sports activities. After receiving the consent forms, the examinees were given enough information regarding the research procedure and their blood samples were obtained in a standard position, collected in pipes containing EDTA, and centrifuged 24 and 48 hours before and after the first and last training sessions, respectively. The obtained plasmas were kept at -80 °C and their serum vaspin concentrations were measured by ELISA method using the special Human Vaspin kit. To analyze the data, the paired and independent t-test and SPSS-21 Software were performed; the meaningfulness level p was considered to be less than 0.05 (p < 0.05). Results: Results showed that after 8 weeks of combined training, the vaspin levels, weight, BMI, WHR, and %BF decreased meaningfully in the training Group compared to the control Group (P <0.05). Conclusions: considering the meaningful vaspin reduction in this study, it seems that combined training (resistance and endurance) is beneficial to obese and overweighed people.